Conjunctival flap surgery for traumatic corneal ulcers: Poster Presentation - Case Report - General practitioner - Anisa Fitri; Yetrina (Majalah Oftalmologi Indonesia, 2023)
Introduction : Trauma was the most common risk factor for corneal ulcers and blindness. Death of corneal tissue due to loss of part of the surface of the cornea is called a corneal ulcer. Conjunctival flap (CF) surgery has an acknowledged role in assuring a stable ocular surface and repressing inflammation in compromised corneas or eyes with reduced visual potential. Case Illustration : 26-year- old male patient came to the Chasan Boesorie Ternate Hospital polyclinic with pain in the left eye after splash cement 3 days before being admitted to the hospital. The left eye is runny, feels itchy, looks red and like there is a block and glare. On ophthalmology status there was a visual acuity OD 6/6, OS 1/300, OS cloudy cornea, hypopion, prolapse of iris and central corneal ulcer with a size of ± 2 x 1 mm. Discussion : The remaining flaps were performed for corneal perforation, graft rejection, bullous keratopathy, and secondary corneal edema. Conjunctival flaps have previously proven to be effective in preserving the globe for individuals with severe ocular surface disease. The flaps promote nutrition, metabolism, structure, and vascularity, as well as reduce pain, irritation, inflammation, and infection. After 6 weeks of surgery visual acuity become better, OS 20/200. Conclusion : Conjunctival flap surgery is an important and useful surgical option of ocular surface disease, especially recalcitrant infectious keratitis and corneal ulcers, particularly in nonresponsive and some perforated cases. CF procedure went well, provides mechanical support for corneal wound healing with good visual outcomes on the patient.